The Role of Stress Management with dhikr-based relaxation techniques in Reducing Teacher Burnout in the Era of Independent Learning Curriculum - Mulyadi, Lintang; Umamah, Uum; Shalahuddin, M.; Norman, Efrita (Ikatan Dai Indonesia, 2024)
This study investigates the effectiveness of a stress management technique using Islamic spiritual practices, known as dzikir, to reduce burnout among high school teachers in the context of an increasing administrative workload under the implementation of the new curriculum. Teachers frequently face high stress levels due to administrative demands, leading to emotional exhaustion, reduced job satisfaction, and lower teaching quality. This research aims to assess the impact of dzikir on alleviating stress and improving emotional and spiritual well-being among teachers. The study employed a quasi-experimental design with a pretest-posttest control group involving 60 high school teachers divided into experimental and control groups. Quantitative data were collected through standardized burnout inventories, and qualitative data were obtained through in-depth interviews. Results indicated that the experimental group, which practiced dzikir, experienced a significant reduction in emotional exhaustion and depersonalization, as well as improved personal accomplishment and job satisfaction compared to the control group. This study concludes that integrating spiritual-based stress management practices is highly effective in addressing burnout among educators, contributing to healthier teaching environments. By emphasizing culturally and spiritually relevant approaches, this research offers a practical solution for enhancing teacher well-being and supports the broader goals of improving educational quality in modern learning systems. These findings underline the importance of incorporating holistic, culturally sensitive interventions into education policy and teacher training programs.